The impact of supplementary materials on students’ english language learning and cultural conceptualization - Rahimipour, Saeid (2021)
The paper has tried to detect the impact of historical, news, and literary supplementary texts on students’ English language skills’ learning and their cultural conceptualization. This research is a true experimental one. Data obtained through questionnaire and open-ended questions’ analyses as well as cross comparison of the means of the groups’ scores were analyzed using SPSS and Max QDA. Also, the paper revealed the advantages it may have culturally, namely participation, social interaction, group cooperation, and cultural conceptualization regarding these groups’ assertions on genre-orientated supplementary materials. It also revealed the effectiveness of the supplementary materials on the students’ language learning and their cultural conceptualization. It clearly showed the superiority of literary materials over the others. Finally, it revealed the better performance of girls on final tests in comparison with the boys. Generally, supplementary materials had a positive impact on the learners’ language learning and cultural conceptualization. They help the learners to understand the culture loaded aspect of language learning and language materials. Hence, the deployment of supplementary materials and above all literary ones is strongly recommended.